SCIENTIFIC TRAINING OF SPORTS MEDICINE FOR BALANCE OF KNEE JOINT MUSCLE STRENGTH OF ATHLETES - Men,Yanhua (2021)
ABSTRACT Introduction: As skiers need to complete their movements in high mountains and snow, the athlete's landing's stability is directly related to the movement's success. The stable landing action wins high scores for the athletes’ participating actions and protects their safety. Objective: This article analyzes the characteristics of lower limb muscle strength and static balance ability of female freestyle skiing aerials athletes to provide athletes with targeted strength training, evaluation of muscle effects after training, and athlete selection to provide a scientific basis valuable Theoretical reference. Methods: The paper uses isokinetic testing and balance testing methods to study the characteristics of the hip and knee flexor and extensor strengths of the Chinese great female freestyle skiing aerials athletes and the static balance characteristics in four standing positions. Results: The right flexor-extensor force, flexor-extensor force ratio, and average power value of the right hip joint were slightly greater than the left flexor power. The left and right knee joint extensor unit peak weight moments and the left and right average power values were all four indicators. Greater than the flexor, at different test speeds of 60°/s (slow speed) and 240°/s (fast), the peak flexion and extension torque per unit weight, the average power of flexion and extension, the force of flexion and extension, and the average power appear with the increase of the test speed as a significant difference. Conclusions: The research in the thesis recommends reasonable weight control and balanced training of muscle strength, using the condition of moderately increasing exercise speed, to strengthen the training of lower limb extensor strength, provide targeted strength training for athletes, evaluate the muscle effect after training and providing the scientific basis and valuable theoretical reference. Level of evidence II; Therapeutic studies - investigation of treatment results.